2006
DOI: 10.1681/asn.2005090936
|View full text |Cite
|
Sign up to set email alerts
|

Alleviation of Sleep Apnea in Patients with Chronic Renal Failure by Nocturnal Cycler–Assisted Peritoneal Dialysis Compared with Conventional Continuous Ambulatory Peritoneal Dialysis

Abstract: Nocturnal hemodialysis has been shown to improve sleep apnea in patients who receive conventional hemodialysis. It was hypothesized that nocturnal peritoneal dialysis (NPD) also is effective in correcting sleep apnea in patients who receive continuous ambulatory PD (CAPD). Overnight polysomnography (PSG) was performed in 46 stable NPD and CAPD patients who were matched for demographic and clinical attributes. The prevalence of sleep apnea, defined as an apnea-hypopnea index (AHI; or frequency of apnea and hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
79
1
7

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 134 publications
(94 citation statements)
references
References 27 publications
(19 reference statements)
7
79
1
7
Order By: Relevance
“…The PSG data in 24 incident PD subjects and body water composition data in 15 of these 24 subjects during NPD and CAPD were reported previously (12). Here, we extended these data by recruiting another 22 incident patients to undergo PSG and magnetic resonance imaging (MRI) of the upper airway during NPD and CAPD.…”
Section: Patientsmentioning
confidence: 56%
See 3 more Smart Citations
“…The PSG data in 24 incident PD subjects and body water composition data in 15 of these 24 subjects during NPD and CAPD were reported previously (12). Here, we extended these data by recruiting another 22 incident patients to undergo PSG and magnetic resonance imaging (MRI) of the upper airway during NPD and CAPD.…”
Section: Patientsmentioning
confidence: 56%
“…Nevertheless, time-averaged intraperitoneal pressure may be higher during CAPD than during NPD because of the permanent load of peritoneal dialysate during the night in CAPD. Theoretically, this may have two effects: (1) changes in respiratory mechanics, such as reduction in vital capacity (27), although recent studies showed that sleep apnea is unrelated to pulmonary function measurements [12,28] and that flow-volume curve indices have no value in predicting sleep apnea (29); (2) more pressure effect on the diaphragm. To maintain the same tidal volume, a more negative intrathoracic pressure has to be generated, which may cause arousal and airway collapsibility, which could in turn lead to sleep apnea.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…309 Recent data support the concept that nocturnal peritoneal dialysis is superior to chronic ambulatory peritoneal dialysis in attenuating sleep apnea as a result of better fluid clearance during sleep. 311 …”
Section: Treatment Of Esrd: Effects On Osamentioning
confidence: 99%